Synthesis and Characterization of Mixed Ligand Complexes Contain Curcumin, Schiff Base and Azide (N3‾) with Some Metal ions and Evaluation their Antibacterial Activity - Sagid M. Lateef (Journal of Global Pharma Technology, 2018)
The research included the synthesis and characterization of new Schiff Base (L3) by reaction 2-aminopyridine and isatin , also included synthesis and characterization of mixed Ligand  complexes using curcumin (essential "HL1", Schiff base (secondary Ligand "L3"), and Azide ion (N3‾) ( secondary Ligand)  with some metal ions and evaluation of antibacterial activity in general formula:  [M(L1)(L3)(N3)H2O]  where : M = [Co(II) , Ni(II) , Cu(II)]  M (L1) (L3) (N3)]       where:  M= [Mn (II), Zn (II), Cd (II), Hg (II)]  With M: L1: L3, 1:1:1 Mole ratio using ethanol as a solvent. The complexes were characterized by using physical methods and spectroscopic (FT -IR, UV-Vis, mass)  along with C.H.N. ,the chloride content and designate the percentage of the metal in addition to measurements of  molar conductivity From the above data we suggested an octahedral geometry for all complexes. Antibacterial activity of ligands and  their complexes was estimated for four types of   bacterial Staphylococcus aureu, Bacillus subtilis, Eterobactern, Escherichia Coli, the results of antibacterial activity showed that their compounds prepared effective against bacteria.Keywords: Curcumin, Schiff base, Mixed ligands complexes.